A 37-Year-Old Man With Fever and Neck Swelling. - Gupta, Nitin; Sebastian, Anjely; Tirlangi, Praveen Kumar; Varma, Muralidhar; Mukhopadhyay, Chiranjay (Clinical Infectious Diseases, 2025)
The article focuses on a case of melioidosis diagnosed in a 37-year-old computer technician from Kerala, India, who presented with fever and right-sided neck swelling. The patient had a history of drinking well water, which may have been contaminated during the monsoon season. Investigations revealed the presence of Burkholderia pseudomallei, the causative agent of melioidosis, confirmed through culture and molecular methods. The patient was treated with antibiotics and showed complete recovery after three months. The case highlights the risk of melioidosis in diabetic patients from endemic regions, particularly those relying on potentially contaminated water sources.